Acupuncture in Poliomyelitis - Zuraida Zulkarnain; Yulfina Bisanto (Indonesian Pediatric Society, 1983)
The purpose of the study is to evaluate the result of acupuncture in the early and late stage of the disease. From January 2974 to December 1977, a total of 276 paralytic cases due to post-poliomyelitis were treated with acupuncture, with the age betseen 3 months and 12 years. Clinically and electromyogram examination were eveluated only on 146 cases. Of the se, 78 cases (53.4%) showed marked improvement, 65 cases (44.5%), showed some improvement and only 3 cases (2.1%) showed no improvement. There is a correlation between the result of the treatment and the duration of the disease. Of the 93 cases starting treatment within one month of the onset of paralysis, 71 cases (76.3%) showed marked improvement, while 22 cases (23.7%) showed some improvement or no improvement. Of the 53 cases starting treatment after one month of the illness, 7 cases (13.2%) showed marked improvement and 46 cases (86.8%)showed some improvement. The technique of the treatment and applicable acupuncture points are described. The method is simple and without risk for the patient.